NaI/PPh3-catalyzed visible-light-mediated decarboxylative radical cascade cyclization of N-arylacrylamides for the efficient synthesis of quaternary oxindoles - Liu, Dan; Zhao, Yue; Patureau, Frederic W. (Beilstein Journal of Organic Chemistry, 2023)
A practical NaI/PPh3-catalyzed decarboxylative radical cascade cyclization of N-arylacrylamides with redox-active esters is described, which is mediated by visible light irradiation. A wide range of substrates bearing different substituents and derived from ubiquitous carboxylic acids, including α-amino acids, were synthesized and examined under this very mild, efficient, and cost effective transition-metal-free synthetic method. These afforded various functionalized oxindoles featuring a C3 quaternary stereogenic center. Mechanistic experiments suggest a radical mechanism.
Keywords: decarboxylative cascade cyclization; iodide catalysis; metal-free photocatalysis; oxindole; phosphine catalysis